2019
DOI: 10.1097/jhq.0000000000000232
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Clinical Outcomes Associated With Intrahospital Transitions

Abstract: Previous transitional care research has focused on transitions occurring between community and hospital settings. Little is known regarding intrahospital transitions and how they affect care quality. A systematic review was therefore conducted to synthesize the literature regarding clinical outcomes associated with intrahospital transitions. Literature published between January 2003 and December 2018 and indexed in Medline/PubMed, CINAHL, and PsychINFO were reviewed using PRISMA guidelines. Articles were limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…2 However, despite being established as an avenue for transmission of pathogens between hospitals, [9][10][11] there is still a lack of clarity around the relationship between intrahospital patient movement and the risk of HAI. 2,12 HAIs are defined as infections which have developed in a hospital or other healthcare delivery setting 48 hours or more following admission, or are present on day 1 or day 2 of admission in a patient discharged in the preceding 48 hours. 13 They place a significant burden on health systems worldwide and lead to increased mortality, intensive care unit (ICU) admissions and longer hospital spells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 However, despite being established as an avenue for transmission of pathogens between hospitals, [9][10][11] there is still a lack of clarity around the relationship between intrahospital patient movement and the risk of HAI. 2,12 HAIs are defined as infections which have developed in a hospital or other healthcare delivery setting 48 hours or more following admission, or are present on day 1 or day 2 of admission in a patient discharged in the preceding 48 hours. 13 They place a significant burden on health systems worldwide and lead to increased mortality, intensive care unit (ICU) admissions and longer hospital spells.…”
Section: Introductionmentioning
confidence: 99%
“…Intrahospital transfers have been variously defined in the literature as any change of location a patient undergoes within the hospital, including transfers between the emergency department (ED) and an inpatient ward, a ward and a procedure room, or two beds on the same ward. 2 Clinical factors such as the need for a procedure or isolation due to infection may require transferring the patient. 3 However, minimal bed availability can also induce extra intrahospital transfers.…”
Section: Introductionmentioning
confidence: 99%
“…12 These transfers require a complex cascade of events and are affected by environmental control and communication challenges, professional conflicts related to variation in culture between units, hospital census and provider workload. 13 In a systematic review, Bristol and colleagues found that intrahospital transfers are frequently associated with adverse outcomes, such as delirium, increased risk of falls, increased length of stay and prolonged duration of mechanical ventilation and central venous catheterisation. 13 This therefore further highlights the significance of intrahospital transfers on patient outcomes.…”
mentioning
confidence: 99%
“…13 In a systematic review, Bristol and colleagues found that intrahospital transfers are frequently associated with adverse outcomes, such as delirium, increased risk of falls, increased length of stay and prolonged duration of mechanical ventilation and central venous catheterisation. 13 This therefore further highlights the significance of intrahospital transfers on patient outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation